PEMBERANTASAN PEREDARAN MINUMAN KERAS DI WILAYAH POLRES PROBOLINGGO - Ma'shum, A. Djazim (JUSTNESS - Jurnal Hukun dan Agama, 2023)
Abstrack The rampant circulation of liquor certainly causes unrest for most of the people, therefore the Government makes a rule regarding the prohibition of the circulation of liquor which consists of Article 300 paragraph 1 and 204 paragraph 1. of the Criminal Code. The approach method used by the author is empirical juridical. The data collection technique used by the author is by means of interviews, documentation studies sourced from related local regulations,. In this study, the authors use primary, secondary, and tertiary data analysis. Efforts to overcome the circulation of liquor by conducting raids, taking action and enforcing the law against violations of the circulation of liquor are guided by the Code of Criminal Law (Kitab Undang-Undang Hukum Pidana). Criminal) and Probolinggo Regency Regional Regulation NO 4 of 2019 concerning the supervision and control of the circulation of alcoholic beverages in Probolinggo Regency. Keywords: Eradication, Liquor